Nations and nationalism since 1780 : programme, myth, reality - Hobsbawm, E. J. (Eric J.), 1917-2012 (Cambridge ; New York : Cambridge University Press, 1992)
Eric Hobsbawm's brilliant enquiry into the question of nationalism won further acclaim for his 'colossal stature ... his incontrovertible excellence as an historian, and his authoritative and highly readable prose'. Recent events in Eastern Europe and the former Soviet republics have since reinforced the central importance of nationalism in the history of political evolution and upheaval. This second edition has been updated in the light of those events, with a final chapter addressing the impact of the dramatic changes that have taken place. It also includes additional maps to illustrate nationalities, languages and political divisions across Europe in the nineteenth and twentieth centuries.
1. The nation as novelty: from revolution to liberalism -- 2. Popular proto-nationalism -- 3. The government perspective -- 4. The transformation of nationalism 1870-1918 -- 5. The apogee of nationalism 1918-1950 -- 6. Nationalism in the late twentieth century -- 1. National conflicts and frontier disputes, 1919-1934. Source: The Times Concise Atlas of World History (adapted with permission) -- 2. Peoples, languages and political divisions in the nineteenth century: the East European linguistic jigsaw. Source: The Times Concise Atlas of World History (adapted with permission) -- 3. Nationalities of the Habsburg empire c. 1910. Source: The Penguin Atlas of World History, vol. II (adapted with permission).
Includes bibliographical references and index.
ENH
Keywords: Nationalism -- History; Nationalism; English language